2021
DOI: 10.1002/ghg.2075
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations and developing multilayer neural network models for prediction of CO2 solubility in aqueous MDEA/PZ and MEA/MDEA/PZ blends

Abstract: In this research, a new set of experimental data for CO 2 solubility in aqueous blended amine solvents were investigated experimentally over the CO 2 partial pressure range from 8 to 100 kPa at 40°C and were compared with the benchmark aqueous 30 wt.% MEA solution. This work developed two multilayer neural network models named models A and B, for predicting the CO 2 solubility in various aqueous blended amine solvents including 36 wt.% MDEA + 17 wt.% PZ, 24 wt.% MDEA + 26 wt.% PZ, and 6 wt.% MEA + 25 wt.% MDEA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Accordingly, this work compared several network structures to improve the prediction performance. Based on the published work, , it was found that ANN might predict the CO 2 equilibrium solubility in single and blended amine solvents. However, the input variables should be properly adjusted to simplify the network based on the type of solvents.…”
Section: Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, this work compared several network structures to improve the prediction performance. Based on the published work, , it was found that ANN might predict the CO 2 equilibrium solubility in single and blended amine solvents. However, the input variables should be properly adjusted to simplify the network based on the type of solvents.…”
Section: Methodologiesmentioning
confidence: 99%
“…Furthermore, it is known that ANN models require sufficient input data for training, so insufficient or excess input data potentially cause over- or underpredictions. In this case, most ANN models from previous work were developed based on sufficient experimental data obtained from different works. , For novel single and blended solvents, missing data are a common issue. If the novel solvent blends are blended by several conventional single solvents, the ANN model can be trained by using the single solvents directly .…”
Section: Methodologiesmentioning
confidence: 99%
“…Deng and Guo [13] developed an artificial neural network model to predict the products of CH4 bi-reforming using CO2 and steam, demonstrating its accuracy with correlation coefficients over 0.995 across various operational conditions. Li et al [14] developed two neural network models to predict CO2 solubility in aqueous blended amine solvents, using extensive experimental data and a backpropagation learning algorithm. The models demonstrated high accuracy, outperforming traditional thermodynamic models, and were particularly effective for complex blended amine systems like MDEA/PZ and MEA/MDEA/PZ.…”
Section: Introductionmentioning
confidence: 99%